Kelly Miller's history of the World War for human rights; an intensely human and brilliant account of the World War; why America entered the conflict; what the allies fought for; and a thrilling account of the important part taken by the negro in the tragic defeat of Germany; the downfall of autocracy, and complete victory for the cause of righteousness and freedom. - Miller, Kelly, 1863-1939. (Tufts University. Tisch Library., 2015)
1 online resource (xiii, 17-608 pages) : illustrations.; Published also with slight variations in text, under title: Our war for human rights.; Spine title: Negro soldier in our war.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University,2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.